State failure and globalization (2007)
State failure, more than a simple «anomaly» in the international system, reveals a deep transformation of statehood under the influence of globalization process. The so called «failed», «collapsed» or «unviable states» correspond only to the most extreme cases of a spectrum in which the limits of statehood «normality» turn out to be difficult to define and the modern concept of state-nation shows its inadequacy regarding the changes in the contemporary state. Therefore the need of a theory that comprises the model or models of statehood that would be in formation under this new global order.